Zinc detection in cosmetics - Jolanta Materna; Barbara Nieradko-Iwanicka (Kazimierz Wielki University, 2020)
Zinc is a metal which participates in the control of genetic information transfer, protein biosynthesis, affects the proper structure of the skin and hair, has bactericidal activity, accelerates wound healing, increases resistance to infection. It has an effect on skin regeneration and affects collagen metabolism. The aim of the study was to check it zinc is present in cosmetics. To detect zinc in cosmetics, 0.2 g were weighed into a 25 cm3 beaker. 5 cm3 of an 80% acetic acid solution was added, the beaker was covered with a watch glass and the contents were heated for 5 minutes. The suspension was cooled, poured into a centrifuge tube and centrifuged. The supernatant liquid was poured onto a watch glass, a few drops of Na2S solution were added. The precipitation of the white ZnS precipitate indicated the presence of zinc in the sample. 105 samples of cosmetics were collected. The compositions of these cosmetics were analyzed. Zinc and its compounds were enumerated by the manufacturers in the composition of 14 cosmetics collected for the study. Presence of zinc was confirmed in Bell HYPOAllergenic - Powder, Face palette Bronze'n'blush no 14 and 24, Skin79 Super + Beblesh Balm,  MaxFactor - Powder, My Secret -  eye shadow, Paese - eye shadow , Ziaja med - soothing treatment, Ziaja GdanSkin - hydrogel face, Tołpa dermo face mask, Mixa - Against imperfections mask, The Ordinary serum, Oriflame Royal Velvet - night cream and BeBeauty Care - face mask. Conclusion: Zinc was detected in 14 cosmetics.